PPAR agonists: I. Role of receptor subunits in alcohol consumption in male and female mice - Blednov, Yuri A. (Alcohol Clin Exp Res, 2016)
BACKGROUND: Several peroxisome proliferator-activated receptor (PPAR) agonists reduce voluntary alcohol consumption in rodent models, and evidence suggests that PPARα and γ subunits play an important role in this effect. To define the subunit dependence of this action, we tested selective PPARα and α/γ agonists and antagonists in addition to null mutant mice lacking PPARα. METHODS: The effects of fenofibrate (PPARα agonist) and tesaglitazar (PPARα/γ agonist) on continuous and intermittent two-bottle choice drinking tests were examined in male and female wild-type mice and in male mice lacking PPARα. We compared the ability of MK886 (PPARα antagonist) and GW9662 (PPARγ antagonist) to inhibit the effects of fenofibrate and tesaglitazar in wild-type mice. The estrogen receptor antagonist, tamoxifen, can inhibit PPARγ-dependent transcription and was also studied in male and female mice. RESULTS: Fenofibrate and tesaglitazar reduced ethanol consumption and preference in wild-type mice, but these effects were not observed in mice lacking PPARα. MK886 inhibited the action of fenofibrate, but not tesaglitazer, while GW9662 did not inhibit either agonist. The PPAR agonists were more effective in male mice compared to females, and drinking in the continuous two-bottle choice test was more sensitive to fenofibrate and tesaglitazar compared to drinking in the intermittent access test. Tamoxifen also reduced ethanol consumption in male mice and this action was inhibited by GW9662, but not MK886, suggesting that it acts by activation of PPARγ. CONCLUSIONS: Our study using selective PPAR agonists, antagonists, and null mutant mice indicates a key role for PPARα in mediating reduced ethanol consumption by fenofibrate and tesaglitazar.